Dynamic networks of interactive learning and agricultural research for development: three critical roles for agricultural advisory services - Maatman, Arno; Wongtschowski, Mariana; Heemskerk, Willem; Sellamna, Nour; Davis, Kristin E. (International Food Policy Research Institute, 2011)
Innovation in natural resource management and agriculture—and in agribusiness, in particular—critically depends on the ability of interlinked actors to generate and access new knowledge, and to adapt such knowledge to their own specific circumstances and in accordance with their individual and joint ambitions. Innovation emerges from innovation systems. This paper takes a closer look at innovation systems, including the various actors involved, their interrelationships, and governance mechanisms. Innovation systems operate at different levels, in terms of structure, functioning, and performance at the national level, and from two different angles: as a macrostructure that involves different functions and key organizations working on these functions, and as the composite of different innovation networks comprising individuals and local and national organizations. In addition, the notion of innovation clusters is used to characterize the network that revolves around a particular challenge (for example, in value-chain development or natural resource management) at a local or regional level.